Ad-hoc, mobile, and wireless networks : 17th International Conference on Ad Hoc Networks and Wireless, ADHOC-NOW 2018, Saint-Malo, France, September 5-7, 2018. Proceedings /: 17th International Conference on Ad Hoc Networks and Wireless, ADHOC-NOW 2018, Saint-Malo, France, September 5-7, 2018. Proceedings. (2018) - Unknown
No abstract available